The Responsiveness of Village Officials in Delivering Population Administration Services During Digital Transformation - Dirgantara Yosef; Siti Khumayah; Moh Sutarjo (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Due to their direct connection to the realisation of citizens' administrative rights, population administration services are an essential component of public services. Advances in information technology are driving the digitalisation of village-level service systems. This study aims to identify the variables that influence the responsiveness of Pegagan Kidul Village officials in delivering population administration services during digital transformation. The study employs a qualitative methodology encompassing interviews, observation, and documentation. Data analysis was conducted through three stages: data reduction, data presentation, and conclusion drawing, with village officials and service users serving as informants. The results indicate that the village officials' responsiveness is generally satisfactory, as demonstrated by their prompt follow-up on requests and assistance with document processing. However, service delivery remains primarily reactive, as information dissemination is not yet proactive. Additionally, the village website and online communication platforms are not yet being utilised to their full potential. Service responsiveness is further affected by systemic limitations within relevant agencies, restricted technology use, and the public's limited comprehension of digital services. It is therefore recommended that capacity building for officials, improved inter-agency coordination, and more extensive public outreach be pursued in order to ensure that service quality can be improved in a sustainable manner.